Science Curriculum in Non-formal Education: Case Study to Improve the Quality of Non-Formal Education - Kurniawan, Aziz; Nawa, Nurul; Rini, Nur Widya (Journal of Nonformal Education, 2026)
This article focuses on the science curriculum in formal education as an effort to improve the quality of non-formal education. The purpose of writing this article is to analyze the implementation of science learning in non-formal education based on the curriculum implemented. This type of research is a qualitative approach case study. The research was conducted at SKB Purwokerto and PKBM Harapan Bangsa. Data was collected through a process of observation and interviews, supplemented by various literature relevant to the topic of discussion. After the data is collected, the writer then analyzes it and ends with drawing conclusions. The research results show that non-formal education in learning planning implements an equality program by adopting an inclusive and differentiated approach. Apart from that, an andragogy approach is also applied to ensure that the science learning carried out is relevant and beneficial for students. The learning process carried out at SKB Purwokerto and PKBM Harapan Bangsa refers to the 2013 curriculum and is flexible because it is adapted to needs. There is a difference between the two non-formal education, namely in the aspect of the depth of the material taught. As in other educational institutions, after implementing the learning process, an evaluation is carried out to determine the achievements of a program